Information Security Applications 12th International Workshop, WISA 2011, Jeju Island, Korea, August 22-24, 2011. Revised Selected Papers - Jung, Souhwan; Yung, Moti.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-workshop proceedings of the 12th International Workshop on Information Security Applications, WISA 2011, held in Jeju Island, Korea, in August 2011. The 21 revised full papers presented were carefully reviewed and selected from 74 submissions. The workshop serves as a forum for new results from the academic research community as well as from the industry; the papers are focusing on all technical and practical aspects of cryptographic and non-cryptographic security applications.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Data Encryption; Management of Computing and Information Systems; Information Systems Applications (incl. Internet).; Systems and Data Security